Evaluating Maternal Mental Health as a Determinant of Child Behavioral Outcomes - Dr Sunita Mor, Dr Rajesh Rathi, Dr Savita Pannu Rathi, Dr Pooja Rathee (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Postpartum mental illness has gained increasing attention fromresearchers, clinicians, and public health professionals. Early detection allows timelyintervention, reducing adverse consequences for the mother, her newborn, otherchildren, and spouse.